Effectiveness of a nutrition and physical activity intervention among adolescent - Bahathig, Abeer Ahmad; Saad, Hazizi Abu; Yusof, Nor Baizura Mohd; Shukri, Nurul Husna Mohd (International Journal of Public Health Science (IJPHS), 2023)
Unhealthy food intake, physical inactivity, and body image (BI) dissatisfaction could potentially lead to obesity and health problems. This cluster-randomized intervention study aimed to investigate the effectiveness of a nutrition and physical activity (PA) intervention on related knowledge, attitudes, and practices among Saudi adolescent girls (aged 13–14) living in Arar City. One hundred thirty-eight girls were selected and recruited randomly from two schools. The respondents in the intervention group (IG; n=68) received a three-month intervention program that consisted of six 90- minute sessions. The participants in the control group (CG; n=70) received only their traditional education and did not receive the intervention program. The groups’ total pre-test scores for practices were significantly different; therefore, the pre-test scores were used as covariates. The IG demonstrated significant improvements in knowledge, attitudes, and practices (p<0.001 for all), and improvement in the IG was greater than that in the CG at the post- test and three-month follow-up time points (p<0.001 for both). These findings provide evidence of the significant influence of a nutrition, PA, and positive BI intervention on related knowledge, attitudes, and practices among Saudi adolescent girls.